Peran Branding dan Digital Marketing dalam Pengembangan UMKM Catering Mekar Wangi (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
Based on various problems affecting MSME partners, training is needed, both formal and informal in digital/online marketing strategies and how to brand products for partners in a larger market. The implementation method used in this community service to provide solutions to the problems faced by MSME partners includes assistance in selecting packaging, assistance, and education on the importance of product hygiene and sanitation, socialization on the importance of branding on products such as logos and product names, and assistance in digital marketing strategies through social media. Based on the results of the community service which include branding in making logos and banners for MSME Catering Mekar Wangi, socialization and assistance related to packaging changes, and the creation of social media accounts as online marketing media, it can be concluded that the community service program in education and assistance in branding and digital marketing on Mekar Wangi Catering products has been running well because MSME partners can gain new knowledge and skills to be applied to their businesses with the aim that Catering Mekar Wangi will be more advanced and its marketing network will be wider in the future and provide an increase in sales turnover for its products.